Studies of Contaminant Factors of Heavy Metals Content in Subsistence Farmlands at Akinyele Local Area in Oyo State, Southwestern Nigeria Using Geochemical Indices - Adetoro Temitope Talabi; Rasak Kola Odunaike; Oladapo Ajiboye (Indonesian Journal of Social and Environmental Issues (IJSEI), 2023)
The consumption of heavy metals through the ingestion of food is a growing concern in developing countries where monitoring of the environmental content of heavy metals has not been given the desired attention. This research work aims at determining the public health risks and safety of farm products in terms of their residual heavy metal burdens from five subsistence farmlands in the Akinyele area. Analysis of concentrations of Cd, Cu, Cr, Pb, Fe, and Zn in soil samples from the study area was conducted using a flame atomic absorption spectrophotometer. The pH of the samples was measured in situ using pH meter while soil organic matter was determined using the loss of ignition method. Geochemical indices were used to determine the concentration trend of heavy metals in the soil samples. Correlation analysis was performed to establish the relationship between the metals. The concentrations of all the heavy metals were below the maximum permissible limit stated by WHO/FAO. The soil pH ranged from 7.36 to 8.38 indicating that the study area is slightly alkaline. The soil organic matter content ranged from 1.637% to 2.1% indicating that the soil from the study area are mineral soils. Geochemical indices revealed that all the sampling sites were uncontaminated except Site A, B, and E with moderate contamination of Cd. Correlation studies between the analyzed variables revealed the common origin of all metals. The study area can be recommended for farming purposes. However, more farmlands should be tested to determine their residual heavy metal concentrations.